The Influence of Continuous Training, Perceived Usefulness and Employee Digital Experience on Employee Trust in Digital HRM Systems of Digital Startup Employees - Fatimah Malini Lubis; Joko Ariawan; Pipit Sundari; Antok Supriyanto; Tri Yusnanato; Anton Nurcahyo (Journal of Information System, Technology and Engineering, 2026)
This study investigates the impact of Continuous Training and Perceived Usefulness, along with Employee Digital Experience, on Employee Trust towards Digital HRM Systems in the context of employees working in digital startups. This study was primarily quantitative and primarily used surveys. The study used purposive sampling. The research made use of Google Forms to create and distribute an online survey. The data was analyzed using multiple linear regression analysis. The results were verified for validity and reliability, and other preliminary assumption tests such as normality, heteroscedasticity and multicollinearity, along with some other preliminary assumption tests, were also conducted prior to the hypothesis tests. Continuous Training, Perceived Usefulness, and Employee Digital Experience were shown to positively and significantly impact Employee Trust in Digital HRM Systems. This was shown to be the case whether the three constructs were analyzed independently, in combination, or as a group, with the study showing that the three constructs were important for the creation of trust in Digital HRM systems. Finally, it is anticipated that this research will provide a theoretical boost to the development of digital human resource management and technology acceptance debates and practical advice to digital startup firms that wish to make their Digital HRM system deployment operate more efficiently.